Evaluation of the LncRNA TMPO AS-1 Expression Level in Breast Cancer Tissues in Comparison with Paired Normal Marginal Tissues. - Niknam, Saman; Zarredar, Habib; Asvadi, Tooraj; Asadi, Milad; Zafari, Venus; Maleki, Raheleh Aligholipour; Shanehbandi, Dariush; Hashemzadeh, Shahryar (Middle East Journal of Cancer, 2026)
Background: Breast malignancy is a major public health problem and one of the prevalent cancers, which leads to death in women all around the world. Long non-coding RNAs (lncRNAs) are widely studied in the pathogenesis of malignancies. Previous studies have confirmed the correlation of lncRNAs and the cellular development and growth of breast malignancy. The present study aimed to evaluate the expression level of long non-coding RNATMPO antisense RNA 1 (LncRNA TMPO AS-1) in breast cancer tissues and compare it with paired normal marginal tissues. Method: 50 breast cancer patients were included in this case-control study and tumor tissues and healthy marginal tissues were collected during surgery. Total RNAs were extracted from the normal and cancerous tissues, and after quality control cDNA was synthesized. The TMPO AS-1 expression level was determined by quantitative polymerase chain reaction (qPCR). The gene expression level and their relationships with the patient's clinicopathological characteristics were analyzed using appropriate statistical tests. Results: TMPO Antisense RNA 1(TMPO-AS1) is significantly high expressed in breast cancer tissues compared with normal peripheral tissues (P-value <0.0001, fold change: 1.16). Among the 40 patients exposed to chemotherapy drugs 5-Fluorouracil (5FU) and doxorubicin, the TMPO-AS1 expression level was significantly decreased as compared with the 10 patients unexposed to chemotherapy (P < 0.0001, fold change: 0.11). Lymph node metastatic patients (29 positive patients, 21 negative patients) showed high TMPO-AS1 expression level than negative lymph nodes metastasis patients (P = 0.0012, fold change = 1.161). Conclusion: We demonstrated that TMPO-AS1 is highly expressed and its up-regulation correlates with the pathogenesis and tumorigenesis of breast cancer.